Ativismo e representações midiáticas em canais LGBTQIA+ no YouTube: um estudo do canal Tá entendida? - Lotufo, Ana Júlia Della Méa (2021)
In this dissertation, we propose to investigate how the activist practices, from the YouTube platform channel Tá Entendida?, contribute to the mediatic representation of lesbians. On the theoretical basis to support our analytical reflection, we present activism notions that bring the understanding of how actions undertaken in the search for social justice integrate daily and mediatic interactions. To support the work, we also appropriate the notion of representations as socially shared symbolic constructions, of the discussion on the limits of mediatic representations, and of the possibility of self-representation of the minoritarian groups in the media. These are the central notions, that support interrelated conceptions that are present in this research. From an initial mapping, we chose the Tá Entendida? channel and, through the observation of all of the videos published in the channel between 2018 and 2020, we listed four thematic groups: 1) affective relationships; 2) acceptance and experiences of lesbians; 3) tags and 4) general subjects. We defined the thematic group 2), coupled with the LGBTQIA+ pride month (June) and the lesbian visibility month (August), from the years 2018, 2019 and 2020, for the cutout to be analyzed accordingly to the analytical axes. We saw the need to understand how the activist actions in the content, the image, and the interactions that are revealed in this channel can re-signify the mediatic representations of these women. The achieved results explain that, in the Tá Entendida? channel, we have, among other aspects, an activism created through first person experiential narratives that are supported in symbolic elements and echo in interactions between the channel’s participants. These interactions show identification with the content, allowing the channel to be appropriated as a welcoming space for the interlocutors to also narrate their experiences. Through the self-representation made by the producers of the Tá Entendida? channel, with content based in experiences lived by them, we can notice the possibility of resignifications on the mediatic representation for lesbians.